Jahresbericht 1996. (Annual Report of the Executive Board; 1996, 1996)
The Annual Report to the Board of Governors reviews the IMF's activities, policies, and organization, as well as the world economy, with emphasis on balance of payments problems, international and emerging capital markets, fiscal considerations in policymaking, data issues, and the debt situation. As part of the IMF's ongoing efforts to improve transparency in its operations, the 1996 Report continues the expanded coverage of economic developments in selected countries and gives details about policy objectives in member countries using Fund resources. The 1996 Report also provides information on the IMF's new data dissemination standard. Appendices include a report on international reserves, details of the IMF's financial operations, major decisions taken by the Executive Board during the year, communiques of the Interim and Development Committees, a list of Executive Directors and their voting power, capital and administrative budgets and information on staffing, and audited financial statements of all IMF accounts and facilites. Published in September.